A superficial density method to describe the diffuser boundary condition in CFD simulation of indoor airflow. (1st May 2018) - Deng, Baoqing; Zhang, Yujie; Long, Fei
Abstract: Diffuser boundary condition is important for the accurate simulation of indoor environment. This paper analyzes the condition of keeping the coupling of mass and momentum boundary condition in CFD. A superficial density method is developed to describe the diffuser boundary condition for the simplified geometry of the diffuser. The present superficial density method is validated through the experimental data from IEA Annex-20 project. Good agreement is obtained between the computation and the experimental data. The present method can be easily implemented in the in-house code and commercial CFD software. Highlights: The coupling condition of mass and momentum boundary condition is analyzed. The superficial density is introduced at the diffuser. The superficial density method is validated through the IEA annex-20 project.